Influence Of Elicitor Availability On Limonene And Linalool Accumulation From Citrus Grandis Cell Cultures. - Nik Abdul Rahman, Nik Norulaini; Zakaria, Zarina; Abdul Kadir, Mohd Omar (2003)

(untitled)
Limonene and linalool are among the active terpenes and major constituent of citrus essential oils. Limonene, the principal component of orange peel oil, has been identified as a non toxic agent with potential for cancer chemotherapy (Hardcastle et al. 1999).